Regional Features Research of Municipal Solid Waste Disposal in Ukraine - Prykhodko, V. Yu. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2019)
Purpose. Analysis of the current state with municipal solid waste disposal based on official statistical information, development of a set of indicators based on the characteristics of regional waste disposal. Methods. Statistical information analysis methods, including method of multivariate statistical analysis - cluster analysis. Results. The development of a set of waste disposal indicators at the national level is based on official statistical information on solid waste generation and disposal, as well as waste disposal services. The analysis of the developed database by regions of Ukraine revealed some deficiencies in the primary information and consi- derable variability of the data. The transition from absolute to specific values is the basis for a set of indicators formation combined into three blocks, which characterizing the generation and disposal of municipal solid waste (5 indicators), waste disposal sites (12 indicators) and socio-economic indicators (3 indicators). For the territory of Ukraine zoning by the situation with the municipal solid waste disposal the cluster analysis method were used. Indicators calculated for 24 regions of Ukraine indicate significant data variability. On the basis of 11 indicators, the zoning of the territory of Ukraine was conducted according to the situation with the municipal solid waste disposal with the definition of four clusters (drawing on the map-scheme of Ukraine) and their generalized characteristics. Conclusions. In order to solve the problem of inter-regional comparison and qualitative analysis of information, it is advisable to move from the primary data on generation and disposal, as well as the provision of municipal solid waste removal services to derived means – indicators. As a result, four clusters of Ukraine regions with generalized characteristics for each group were obtained. According to the results of clustering, we can conclude that the worst situation is in Kyiv and Lviv regions. The best situation of municipal solid waste disposal (by a set of indicators) is in Volyn, Dnipropetrovsk, Kirovohrad, Odesa and Chernihiv regions.